2007
DOI: 10.1097/01.hcr.0000281772.28394.30
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Physical Performance in Land- and Water-Based Pulmonary Rehabilitation

Abstract: Clinicians can consider water-based PR exercise program as another treatment option, if available, for patients with COPD and expect similar benefits to traditional land-based PR programs including improved walk distances, strength, and perception of well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 9 publications
0
25
0
2
Order By: Relevance
“…The muscle strength of the shoulder flexors and of the knee extensors of the dominant limbs was assessed using the 10-RM with ankle and free weights. In patients with COPD, the completion of 1-RM testing may not be advisable or safe 14 ; thus, 10-RM has been used. 15 The 10-RM was considered the maximum amount of weight that could be moved through the full range of motion 10 times with the proper technique and without compensatory movements.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…The muscle strength of the shoulder flexors and of the knee extensors of the dominant limbs was assessed using the 10-RM with ankle and free weights. In patients with COPD, the completion of 1-RM testing may not be advisable or safe 14 ; thus, 10-RM has been used. 15 The 10-RM was considered the maximum amount of weight that could be moved through the full range of motion 10 times with the proper technique and without compensatory movements.…”
Section: What This Paper Contributes To Our Knowledgementioning
confidence: 99%
“…Although water-based exercise training has been shown to provide additional advantages in terms of improvements in peak and endurance walking capacity and self-reported quality of life compared to land-based training in a quasi-randomized trial, 20 these positive benefits were not consistently shown in the observational and retrospective trials. 22,23 The lack of conclusive findings may relate to both the quality of the studies reviewed (i.e. poor methodology and design) and the quality of the exercise prescription and training.…”
Section: Discussionmentioning
confidence: 99%
“…Other non-randomized trials investigating the effects of exercise training in water on people with COPD include an observational study 22 and a retrospective study. 23 In a single group observational study investigating swimming pool-based exercise as pulmonary rehabilitation, 101 patients with COPD identified from a general practice computer disease register were invited by letter to join the trial. 22 Twenty-four patients expressed an interest but only 16 participants started the water-based pulmonary rehabilitation program.…”
Section: Effects Of Exercise Training In Water In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, members of the rehabilitation team at BMFLCC answered these unaddressed questions and proceeded to develop one of the first water-based pulmonary rehabilitation programs that published outcomes comparing water-and land-based programs. A study comparing results of 20 participants in the aquatics program with 20 matched participants in the land-based program showed equivalent results, with all showing significant improvements in physical performance and quality of life measurements (12). Currently, patients can access an aquatic rehabilitation program offered at the Baylor Institute for Rehabilitation Aquatics Center as part of the BMFLCC pulmonary rehabilitation program during summer months.…”
Section: Disease-specific Strategiesmentioning
confidence: 95%